Does it really help? Exploring the impact of Al-Generated writing assistant on the students English writing - Regina Rahmi; Zahria Amalina; Andriansyah Andriansyah; Adrian Rodgers (Universitas Syiah Kuala, 2024)
The increasing use of tools that assist English as a Foreign Language (EFL) learners in achieving writing fluency has drawn attention to the rapidly evolving role of AI in education. This study evaluates an AI-generated writing assistant in English language learning, that is the ParagraphAI text generator, focusing on its potential impact and effectiveness for L2 learners writing skills. This AI-powered writing software curates writing content according to writers preferences. Four seventh-semester EFL students were selected using homogeneous purposive sampling. Data collection involved tests and questionnaires, with subsequent analysis including text comparison to measure Lexical Diversity indices, followed by descriptive analysis. The results indicate that while the AI writing assistant aids in correcting grammatical errors and enhancing text cohesion and coherence, it lacks content density at times. In some instances, the intended message and thoughts of the students were not effectively conveyed, leading to the inclusion of ideas unrelated to the initial topic. This study underlines the importance of considering linguistic and content-related aspects in evaluating AI-generated writing assistants. While the tool enhances grammatical accuracy and structural coherence, further refinement is needed to address deficiencies in content density. The analysis of four seventh-semester EFL students offers valuable insights into the evolving AI in education, prompting considerations for optimizing these tools to better meet the diverse needs of language learners and educators.